POLITICAL MARKETING OF THE DARMA WIJAYA–ADLIN UMAR YUSRI TAMBUNAN PAIR IN THE 2020 SERDANG BEDAGAI (SERGAI) REGIONAL ELECTION - Junaidi; Mahmud Yunus Daulay (Journal of Social Science, 2026)
Objective: Direct regional head elections in Indonesia require candidate pairs to adopt effective political marketing strategies to win the support of increasingly fragmented voters. This study investigates the political marketing strategies used by the Darma Wijaya–Adlin Umar Yusri Tambunan (“Dambaan”) pair in the 2020 Serdang Bedagai (Sergai) Regent Election, which successfully defeated the two-term incumbent. Using Niffenegger’s 4P marketing mix theoretical framework (Product, Promotion, Price, Place) and Nursal’s push–pull–pass typology, this study aims to identify the target domains, media channels used, drivers and barriers to constituent support, communication strategies, and perceptions of the realization of campaign promises after the inauguration. Method: Using an embedded mixed-methods design, data were collected through questionnaires with 21 respondents, in-depth interviews with key informants of the campaign team, and documentation studies during the first 100 days of the administration. Results: The findings indicate that the pair's victory relied heavily on a push marketing strategy through grassroots engagement (blusukan) and pass marketing mediated by youth and religious organizations (such as Pemuda Pancasila and GP Ansor), which served as the primary channel, replacing expensive digital infrastructure. Constituent support was driven by personal closeness and trust established long before the candidacy, while opposition stemmed primarily from residual loyalty to the previous incumbent. Novelty: Post-inauguration, the majority of respondents expressed satisfaction with the pair's initial performance, particularly in infrastructure and irrigation improvements, indicating that marketed promises were followed up with concrete governance.